2003
DOI: 10.1002/aic.690490123
|View full text |Cite
|
Sign up to set email alerts
|

Fuel options for solid oxide fuel cells: A thermodynamic analysis

Abstract: ( ) The eligibility of natural gas methane , methanol, ethanol, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 17 publications
3
44
0
Order By: Relevance
“…SOFCs have the ability to operate at high temperatures in the range of 973-1273 K. The electrolyte of a SOFC is a solid, what makes it better than molten carbonate fuel cell, which also operates at high temperatures (923 K) and can tolerate impurities. SOFC has the ability to utilize variety of fuels: hydrogen, methane, syngas, biogas and products of SR which are mixtures of hydrogen, carbon monoxide, carbon dioxide, steam and methane [16]. Internal reforming improves heat balance and cools down FC.…”
Section: Introductionsupporting
confidence: 41%
“…SOFCs have the ability to operate at high temperatures in the range of 973-1273 K. The electrolyte of a SOFC is a solid, what makes it better than molten carbonate fuel cell, which also operates at high temperatures (923 K) and can tolerate impurities. SOFC has the ability to utilize variety of fuels: hydrogen, methane, syngas, biogas and products of SR which are mixtures of hydrogen, carbon monoxide, carbon dioxide, steam and methane [16]. Internal reforming improves heat balance and cools down FC.…”
Section: Introductionsupporting
confidence: 41%
“…Performances of external reforming SOFCs (ER-SOFC) fed by different fuels, e.g. methane, methanol, ethanol, and gasoline, were compared within a temperature range of 800-1200 K [4]. It was observed that at low temperatures, methane required a lower inlet steam:fuel ratio to prevent unfavorable coke formation than did methanol and ethanol.…”
Section: Introductionmentioning
confidence: 39%
“…One available option is the use of alcohols (e.g. methanol, ethanol, DME) in an SOFC generator with internal or in-stack fuel reforming to provide power to high energy-demanding auxiliary units [3]. Methanol is a good candidate since it is readily available, but usually a fossil fuel such as natural gas or coal is used as the initial feedstock.…”
Section: Introductionsupporting
confidence: 42%
“…( ) ... [1] ... [3] The value representative of the cell voltage is the mean of the voltage values calculated at each discretised sector (or element) along the tube length.…”
Section: Formatted: Bullets and Numberingmentioning
confidence: 45%